2015
DOI: 10.1134/s1995425515030130
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bacillus spp. on strawberry gray-mold causing agent and host plant resistance to disease

Abstract: The influence of Siberian strains of bacteria Bacillus spp. on the strawberry gray mold causative agent and plant resistance to the disease in three seasons differing in growing conditions has been studied. Bacterial strains B. subtilis, B. amyloliquefaciens, and B. licheniformis suppress the development of the phyto pathogenic fungus B. cinerea in vitro and in vivo. In addition to the antifungal action, bacterial strains show a positive effect on the growth and development of strawberry plants, indicating mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…(95.3 %) due to the synthesis of surfactin [26]. Shternshis et al [2] tested strains of Bacillus under laboratory conditions and found they suppressed the growth of the phytopathogenic fungus B. cinerea in the range of 70 % (for B. licheniformis) to 100% (for B. subtilis, B. amyloliquefaciens). The inhibitory effect depended on the concentration of the tested bacterial suspension and was achieved at the highest concentration (10 6 CFU/ cm 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(95.3 %) due to the synthesis of surfactin [26]. Shternshis et al [2] tested strains of Bacillus under laboratory conditions and found they suppressed the growth of the phytopathogenic fungus B. cinerea in the range of 70 % (for B. licheniformis) to 100% (for B. subtilis, B. amyloliquefaciens). The inhibitory effect depended on the concentration of the tested bacterial suspension and was achieved at the highest concentration (10 6 CFU/ cm 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Grey mould, caused by the fungus B. cinerea, is one of the most significant agricultural phytopathogens that can infect plants throughout all stages of their growth. For example, in cold and damp weather conditions it can affect strawberry plants, attacking the flowers, leaves, and mature fruit [1,2]. B. cinerea produces large amounts of conidia that are widespread in the air and can be readily transported by wind over long distances.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations